2005
DOI: 10.1515/1538-0653.1386
|View full text |Cite
|
Sign up to set email alerts
|

Trade Potentials in Gravity Panel Data Models

Abstract: The paper shows how - using as an example the trade flows between eleven European countries and 31 OECD `reporting' countries - the result of a gravity model, in terms of potential trade, changes substantially when country heterogeneity and dynamics are taken into account. Comparing the in-sample trade potential index derived from various estimators yields three different results: (a) the average trade potential index poorly represents the distribution of yearly trade potentials; (b) the index converges to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 25 publications
0
21
0
1
Order By: Relevance
“…Fromapurelyeconometricpointofview,wehaveadoptedatheoreticallybasedgravitymodelà la Anderson and van Wincoop (2003) by including countries' fixed effects, in a slightly different way from suggestions by Baldwin and Taglioni (2006) and Baier and Bergstrand (2007), because thenumberofobservationsfortheCEECsampleprovidesinsufficientdegreesoffreedomforthe estimationof2NT(N=countries,T=years)dummiesforunidirectionaltradeinaSystemGMM. Hence, we have adopted the approach suggested by De Benedictis et al (2005) by including exportingandimportingcountries'fixedeffects(α i andδ j respectively),andacountry-pairtimevarianttrendvariablecalculatedastheinteractionbetweentemporaltrendsandfixedeffectsfor countrypairs(trend ijt ). WehavealsoadaptedtheHMRtwo-stageprocedureinapanelsetting,byalsoincludingatimevariant control variable for firms' heterogeneity, using a first-stage probit selection equation (fhet ijt )andthestandardinverseMillsratio(mills ijt ).Inordertoincludespecifictransactioncosts related to firms' heterogeneity that are not included among the regressors of the second-stage estimation, we have used a standard dummy variable for the existence of a common language, which strongly affects the formation of trading relationships.…”
Section: Econometricspecificationanddatasetdescriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fromapurelyeconometricpointofview,wehaveadoptedatheoreticallybasedgravitymodelà la Anderson and van Wincoop (2003) by including countries' fixed effects, in a slightly different way from suggestions by Baldwin and Taglioni (2006) and Baier and Bergstrand (2007), because thenumberofobservationsfortheCEECsampleprovidesinsufficientdegreesoffreedomforthe estimationof2NT(N=countries,T=years)dummiesforunidirectionaltradeinaSystemGMM. Hence, we have adopted the approach suggested by De Benedictis et al (2005) by including exportingandimportingcountries'fixedeffects(α i andδ j respectively),andacountry-pairtimevarianttrendvariablecalculatedastheinteractionbetweentemporaltrendsandfixedeffectsfor countrypairs(trend ijt ). WehavealsoadaptedtheHMRtwo-stageprocedureinapanelsetting,byalsoincludingatimevariant control variable for firms' heterogeneity, using a first-stage probit selection equation (fhet ijt )andthestandardinverseMillsratio(mills ijt ).Inordertoincludespecifictransactioncosts related to firms' heterogeneity that are not included among the regressors of the second-stage estimation, we have used a standard dummy variable for the existence of a common language, which strongly affects the formation of trading relationships.…”
Section: Econometricspecificationanddatasetdescriptionmentioning
confidence: 99%
“…CEEC countries joining the EU should have benefited from the European tradeintegrationprocess;thusthevariableassumesvalue0uptothemomentwhenthecountry entered the EU, and value 1 thereafter. In particular, the variable ENL ijt embodies the so-called 'announcement effect' of the entrance of the eight new member countries into the EU (De Benedictis et al, 2005;Paas, 2001, Sapir, 2001, corresponding to the date of the European Council meeting of Laeken in December 2001. Hence, the dummy assumes the value of 1 as of 2002forallEUcountry-pairsinvolvedintheenlargementprocess.…”
Section: Econometricspecificationanddatasetdescriptionmentioning
confidence: 99%
“…The GMM model is one of the methodologies most used to estimate dynamic gravity models (Jung, 2009). However, as argued in Blundell & Bond (1998), when the data are highly persistent -as in the case of bilateral trade flowsthis procedure can be improved through the estimation by System GMM (De Benedictis & Vicarelli, 2005). It has been shown that when the lagged values of the series approach a unit root, these instruments contain little information about the endogenous variables in differences.…”
Section: Estimation and Resultsmentioning
confidence: 99%
“…In the case of the gravity model, first-differencing the equation removes the fixed effect but also the time invariant regressors from the specification and, when the regressors are of interest, the resulting loss of information may be a serious drawback (De Benedictis, Vicarelli 2005). Moreover, with highly persistent data and short panel (along the time dimension), as in the case of bilateral exports flows and of our dataset specifically, the GMM estimator may suffer marked small sample bias due to weak instruments (Blundell, Bond, 1998).…”
Section: Dynamic Gravity Equationmentioning
confidence: 99%